Growth, microstructure, energy–storage and dielectric performances of chemical–solution NBT–based thin films: Effect of sodium nonstoichimometry. Issue 8 (1st June 2018) - Yang, C.H.; Yao, Q.; Qian, J.; Han, Y.J.; Chen, J.
Abstract: Na0.5+δ Bi0.5 (Ti0.96 W0.01 Ni0.03 )O3 thin films with various Na contents (abbreviated as Na.5+δ BTWN, δ = − 3.0, − 1.5, 0, 1.5%) were fabricated on ITO/glass substrates using a chemical–solution process. The effects of Na nonstoichiometry on the microstructure, insulating, ferroelectric and dielectric performances are investigated. The pure perovskite phase can be obtained in Na0.5 BTWN and Na0.515 BTWN, while for Na0.470 BTWN or Na0.485 BTWN, the main composition contains secondary phase of TiO2 . The grain size increases from 30 nm at δ = − 3.0% to 55 nm at δ = 0%, then decreases to 52 nm with δ = 1.5%. The leakage current of Na0.485 BTWN sample is reduced dramatically in comparison with Na0.5+δ BTWN (δ = − 3.0, 0, 1.5%). The big recoverable energy–storage density of 63.1 J/cm 2 and high energy–storage efficiency of 55.0% can be obtained for Na0.485 BTWN due to the improved electric break–down strength and large difference value between the remanent polarization and maximum polarization. Enhanced dielectricity is achieved in Na0.485 BTWN with a high tunability of 36.0% and a figure of merit of 4.0 at 450 kV/cm and 500 kHz. These results demonstrated that the crystallization, micrographs and energy storage and dielectric properties of Na0.5 Bi0.5 TiO3 are highly sensitive to low levels of Na–site nonstoichiometry.